Simultaneous effects of microalgae in wastewater treatment and microplastic agglomeration - Ho, Hwei Ning (2024)

(untitled)
Microplastics as the emerging contaminants and excess nutrient content in the water bodies cause detrimental effects on the water quality. The microplastic and nutrients can be eliminated by using microalgae. In this study, PVC resin was used as the microplastic contaminant, being immersed in the synthetic wastewater that was added with fertilizer containing Nitrogen and Phosphorus contents. Chlorella Vulgaris was used to treat the contaminants in synthetic wastewater. The microalgae with microplastic were cultured in separate conical flasks for 11 days. Nutrient removal, dry biomass collection, microscopy observation, and FTIR spectroscopy were conducted after cultivation. This study also investigates the interaction between microplastic and microalgae in agglomeration. The Chlorella Vulgaris performed nutrient removal of 99.2% in synthetic wastewater. The PVC resin being introduced into microalgae did not inhibit the algal growth but promoted the growth showing a rise of dry biomass generated 2.81 g/L from 0.77 g/L. Microalgae and microplastic agglomerated and formed flocs were observed in physical observation. Some gel-like liquids were observed between PVC and Chlorella Vulgaris under the microscope. We hypothesized that the presence of extracellular polymeric substances (EPS) was secreted by microalgae to aggregate with microplastic. The functional group of microalgae such as protein (C=C bond, 1635 cm-1 ) of primary amide, (N-O bond, 1540 cm-1 ) of secondary amide, lipids (C-H bond, 2922 cm-1 ), and carbohydrate (CO bond, 1054 cm-1 ) of polysaccharide were obtained through FTIR spectroscopy. Thus, microalgae was considered a feasible treatment to remove excess nutrients and microplastic in wastewater treatment, as the flocs sediment can be harvested from the wastewater